2013 International Conference on Clean Electrical Power (ICCEP) 2013
DOI: 10.1109/iccep.2013.6586904
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop bandwidth impact on MVSA for rotor broken bar diagnosis in IRFOC double squirrel cage induction motor drives

Abstract: This paper investigates the detectability of rotor broken bars in indirect rotor flux oriented control (IRFOC) for variable speed double cage induction motor drives, using vibration signature analysis techniques. The Impact of the closed loop control system cannot be neglected when the detection of rotor asymmetries in the machine is based on the signature analysis of electrical or mechanical variables. Therefore, the investigation of rotor fault components for different bandwidths of closed-loop regulators is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Detecting this fault under a closed loop control is a challenge for many researchers. Therefore, many control techniques have been used and applied, such as field oriented control (FOC), direct torque control (DTC) [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Detecting this fault under a closed loop control is a challenge for many researchers. Therefore, many control techniques have been used and applied, such as field oriented control (FOC), direct torque control (DTC) [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…mask the fault effect [9,10]. Therefore, using stator current analysis causes a difficulty in fault detection, which motivated researchers attempted to use other quantities for fault analysis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The most popular techniques for fault detection in induction motors are the motor current signature analysis (MCSA) and the motor vibration signature analysis (MVSA). There are several current analysis techniques in literature about the identification of faults in induction motors such as broken bars [2,[5][6][7][8][9][10][11] and also vibration analysis techniques [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. When it comes to vibration analysis techniques, there are several methodologies for the detection of broken bars.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al analyzed the vibration signal using an Artificial Neural Network (ANN) for motor fault detection [12]. Gritli et al investigated the impact of the control system related to fault diagnosis; they concluded that current signal is affected and vibration analysis showed better result for fault diagnosis [13]. Betta et al proposed a vibration analyzer based on a digital signal processor (DSP) for fault diagnosis in rotating machine [16].…”
Section: Introductionmentioning
confidence: 99%